Selective hydrodechlorination of trichloromethane to dichloromethane over bimetallic Pt-Pd/KIT-6: Catalytic activity and reaction kinetics - Lee, Sae Rom; Cho, Jae Min; Son, Minji; Park, Myung June; Yong Kim, Woon; Kim, Sang Yob; Bae, Jong Wook (Chemical Engineering Journal, 2018)
Selective hydrodechlorination (HDC) of trichloromethane (TCM, CHCl3) to dichloromethane (DCM, CH2Cl2) was studied on the mesoporous bimetallic Pt-Pd/KIT-6 to verify the roles of the active bimetals to catalytic activity and product distribution. The optimal bimetal ratio of 2 wt%Pt-0.05 wt%Pd on the highly ordered mesoporous KIT-6 calcined at 400 °C showed a maximum TCM conversion with DCM yield, and the optimal calcination temperature of Pt-Pd/KIT-6 was mainly responsible for the formation of homogeneously and closely distributed smaller Pt-Pd nanoparticles with higher oxidation states of Pt crystallites supported by XPS and EXAFS analysis. Based on the proposed kinetic models on the optimal Pt-Pd/KIT-6, the competitive reaction mechanisms of the formations of CH4 and monochloromethane (MCM, CH3Cl) from DCM intermediate can well explain the product distributions. Using the seven different kinetic models, the best model on the basis of the Akaike's Information Criteria showed the activation energies of the HDC of TCM to be in the range of 18–60 kJ/mol. The kinetic model also revealed the inverse relationship between the conversion of TCM and selectivity to DCM. Either an increase of space velocity or decrease of H2/TCM ratio increased the DCM yield, while there existed the optimal operating conditions. The DCM productivity of 1.5 mol-DCM/(gcat·h) was achievable at the highest space velocity and lowest H2/TCM ratio under a specific reaction condition of 190 °C and 0.1 MPa.
Keywords: Akaike's information criterions; Competitive reactions; Hydrodechlorination; Hydrodechlorination (HDC); Inverse relationship; Optimal operating conditions; Product distributions; Trichloromethane; Dichloromethane (DCM); Pt-Pd/KIT-6; Reaction kinetics; Selective hydrodechlorination (HDC); Trichloromethane (TCM)